THE ROLE OF THE EUROPEAN UNION IN HANDLING SYRIAN REFUGEES - Ria Silviana (Faculty of Law Universitas Lampung, 2019)
The EU is a European regional organization which was initially formed due to the economic issue. After that, the EU’s focus expanded to the issue of refugees. Nowadays, the EU’s problem of refugees was caused by the phenomenon of the Arab Spring or Arab revolution that occurred in several Arab countries. Including Syria, which is part of this phenomenon. As a result of the rebellion against the Bashar al-Assad government in Syria, then causing humanitarian problems made the Syrian people feel unsafe to live in their own country, so they sought protection in various countries, including going to European countries. They thought that Europe is a safe area and looks better to provide protection for them. But not all of the EU Member States are able and willing to accept the number of refugees that arrived in their country, even though the EU has the regulations regarding refugees protection. So, the EU’s role is needed to handle the Syrian refugees in its Member States.